2023
DOI: 10.1186/s12966-023-01445-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in children’s and adolescents’ dietary intake after the implementation of Chile’s law of food labeling, advertising and sales in schools: a longitudinal study

Abstract: Background In June 2016, a comprehensive food policy was implemented in Chile that included front-of-package warning labels on key nutrients of concern (total sugars, added saturated fats, sodium, and calories), child-directed food advertisement bans, and school regulations. The policy was implemented in 3 phases from 2016 to 2019 and the primary objective was to improve children’s food environments. This study’s objective was to assess changes in child and adolescent intake of key nutrients of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In Chile, if the content of CNs associated with NCDs exceeded predetermined criteria, the black octagonal FOPWL must be displayed on the front of the product packaging [ 35 , 36 ]. Schnettler et al [ 43 , 44 ] assessed the influence of consumers’ perceived healthfulness, purchase intention, and willingness to pay for reformulated frankfurters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Chile, if the content of CNs associated with NCDs exceeded predetermined criteria, the black octagonal FOPWL must be displayed on the front of the product packaging [ 35 , 36 ]. Schnettler et al [ 43 , 44 ] assessed the influence of consumers’ perceived healthfulness, purchase intention, and willingness to pay for reformulated frankfurters.…”
Section: Discussionmentioning
confidence: 99%
“…The third-phase threshold was implemented in 2019. When the content of energy, total sugar, saturated fat, and sodium in products exceed the threshold, the front of the packaging must be labeled with a black octagonal FOPWL [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Three years after the intervention, total sugars consumed by children at school decreased 11.8 percentage point (pp), saturated fats decreased 1.1 pp, and sodium decreased 10.3 mg/100 kcal. In adolescents, total sugars and saturated fats consumed at school decreased 5.3 pp and 1.5 pp, respectively [17]. In 2022, the Chilean Ministry of Education reported that school-age children decreased their prevalence of obesity by 4.8% relative to 2021 [18], which suggests promising results for countries implementing similar interventions, such as Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…The Chilean regulations were implemented in three phases (2016, 2018, and 2019). Initial evaluations of the Chilean policy after the first phase found that it was associated with changes in the food environment, including reductions of nutrients of concern in the food supply (e.g., energy, sugar, sodium, and saturated fat) 2 and reductions in children's exposure to unhealthy food advertising and marketing [3][4][5][6][7] , improvements in mothers' understanding of unhealthy foods and use of the warning labels 8 , reductions in purchases of foods and drinks carrying the warning label [9][10][11] , improvements in the nutritional quality of foods available in schools 12 , and improvement in children's dietary intake 13 . However, much less is known about policy-linked changes in dietary behavior over a longer time period.…”
Section: Introductionmentioning
confidence: 99%